Vascular ring diagnosis following respiratory arrest. (3rd June 2014) - Robson, Evie Alexandra; Scott, Alison; Chetcuti, Philip; Crabbe, David
Abstract : Vascular rings can present with non-specific respiratory and/or oesophageal symptoms. Early diagnosis requires a high index of suspicion. This case report describes an uncommon acute presentation of a vascular ring. We report a thriving 14-month-old child with a long history of recurrent wheeze and 'noisy breathing'. He presented acutely with food bolus impaction in the oesophagus which led to a respiratory arrest. Oesophagoscopy and bronchoscopy suggested vascular ring anomaly. A contrast-enhanced CT scan demonstrated a right-sided aortic arch with left ligamentum arteriosum encircling the oesophagus and airway. The ligament was ligated and divided. At follow-up 6 months later, the infant had mild persistent stridor but was otherwise well.